TECHNOLOGIES OF CREATING SPELL CHECKER - Riezina О. В.; Kosiuh Р. М. (Journal of Information Technologies in Education (ITE), 2019)
Spell checkers are created to control and correct mistakes in a user document. They are based on the comparison of every word against the spelling dictionary and on the use of correct spelling detection algorithms. The article dwells on technologies of creating spell checker, as well as methods of teaching this technology. Spell checker by Peter Norvig has been studied. Modifications for this program necessary to process Ukrainian texts have been defined. Approach to implementation of language model, that is creating spelling dictionary, based on the Ukrainian Brown Corpus has been suggested. Peculiarities of designing a regular expression for distinguishing words in Ukrainian text have been defined. Texts containing Ukrainian subtitles, created within the volunteer translation project «To Be Announced», have been used as a means of test material for the spell checker. The program that processes this text material in order to check spelling has been described and the obtained results have been analysed. The obtained resulted were concluded to be correct, which encourages further research.